DEVELOPING UNIVERSITY STUDENTS’ INTERCULTURAL COMMUNICATIVE COMPETENCE IN INFORMAL LEARNING ENVIRONMENT: PHOTOVOICE-BASED COLLABORATIVE-REFLECTION TASKS - Abd Rahman; Devi Novitasari (STKIP PGRI Jombang, 2020)
Although much research on the use of photovoice for learning purposes in a higher education context has been well-documented for decades, literature rarely indicate that photovoice has been used as a learning tool to develop intercultural communicative competence particularly in an informal learning environment. To fill this void, this paper reports how photovoice-mediated collaborative-reflection tasks help university students engaged in intercultural learning and develop their intercultural communicative competence. This narrative case study revealed that intercultural communicative competence was detected between the groups (A & B): attitude of curiosity and openness, knowledge of self and other, skills of interpreting and relating, skills of discovery and interaction, and critical cultural awareness. However, critical cultural awareness and attitude of curiosity and openness appeared frequently within both groups. The implication of this study informs the need for applying photovoice-based collaborative reflection in order to develop students’ intercultural communicative competence in informal learning environment.